Adventures with atoms and molecules : chemistry experiments for young people - Mebane, Robert C.; Rybolt, Thomas R. (Hillside, N.J. : Enslow Publishers, 1985)
Chemistry experiments for home or school demonstrate the properties and behavior of various kinds of atoms and molecules.
Includes indexes.
8.1
5-8.
Keywords: Chemistry -- Experiments -- Juvenile literature; Chemistry -- Experiments; Experiments; Molecules -- Experiments; Chemistry -- Experiments; Molecules -- Experiments